Use of Cyproheptadine as an Appetite Stimulant in Children with Cancer - Arzu Yazal Erdem; Suna Emir; Hacı Ahmet Demir; Bahattin Tunç (Güncel Pediatri)
Introduction: Malnutrition is frequently seen in pediatric cancer patients. It is very important to evaluate the nutritional status at diagnosis in these patients. The preferable method to treat cancer associated malnutrition in children is to increase their oral food intake with the help of stimulating their appetite. There are some studies supporting the use of appetite stimulants in patients with chronic illness. In this report, our aim is to share our experience with cyproheptadine as an appetite stimulant in children with cancer. Materials and Methods: The medical records of 14 children who were used cyproheptadine as an appetite stimulant were retrospectively evaluated. Their weight, height, body mass index, weight for age Z-score, appetite status and side effects were recorded at baseline, 4th week and 8th week. Results: Cyproheptadine was used in fourteen patients with a median age of 4.5 (range:2.25-16.5 years). Eleven of them demonstrated a response to cyproheptadine (average weight gain was 1.44 kg) Mean weight-for-age z-score was increased from -2.22 to -1.56 (p<0.05). No serious adverse events due to cyproheptadine were reported. Conclusions: It seems that cyproheptadine is a safe and effective agent to stimulate appetite and weight gain in children with cancer, particularly in short term usage.